Secukinumab Therapy in Refractory Juvenile Idiopathic Arthritis - Meghan Corrigan Nelson DO; Cynthia K. Manos MD, MSCE (SAGE Publishing, 2023)
Juvenile idiopathic arthritis (JIA), the most common chronic rheumatologic condition in childhood, remains a cause of significant morbidity, particularly in those with spondyloarthropathy, including psoriatic arthritis (PsA) and enthesitis-related arthritis (ERA). While secukinumab was recently approved for the treatment of children and adolescents with ERA and PsA, there is limited published data on its use in JIA, particularly in refractory cases, despite its efficacy in the treatment of adult arthritis. We aim to examine the use of this therapy in JIA in a single pediatric rheumatology center. A retrospective chart review was performed and 10 JIA patients who received treatment with secukinumab were identified. Data extracted included disease activity, patient demographics, comorbidities, medications, and laboratory data. Seven ERA, 2 PsA, and 1 poly JIA patient were treated with secukinumab at our center between April 2011 and July 2021. These patients had notably resistant disease, with a mean disease-modifying antirheumatic drug (DMARD) failure rate of 3.8. One hundred percent of patients who underwent magnetic resonance imaging (MRI) after being on at least 3 months of secukinumab therapy demonstrated improvement in their MRI findings. One patient developed a flare of uveitis while on secukinumab therapy, with no other adverse events recorded in our patients. Secukinumab therapy was recently approved for children and adolescents with ERA and PsA, and may offer an efficacious option given its demonstrated improvement in imaging and joint examination, as well as qualitative reports of pain, even in those who have failed other therapies. However, caution may be warranted in those with a history of uveitis and warrants further study.